Identification of Residential and Commercial Area using Convolutional Neural Network - Valliappan Raman; Putra Sumari; Prabhavathy M; Sundresan A/L Perumal (Universiti Sains Islam Malaysia, 2024)
Malaysian Journal of Science Health & Technology, Volume 10 Issue 2 Page (165–175)